Семантико-синтаксична залежність суб'єкта процесу у поетичних творах Тараса Шевченка - Масицька, Тетяна (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено семантико-синтаксичну залежність суб’єкта процесу в семантико-синтаксичній структурі речення. Вказано, що здатність предикатних одиниць із семантикою процесу формувати семантико-синтаксичну залежність суб’єкта процесу, впливає на утворення структури семантично елементарного простого речення. Виділено лексичні групи предикатів процесуального значення. The article researches the semantic and syntactic dependency of the process subject. The research has shown that the ability of predicate units with the process semantics to form the semantic and syntactic dependency of the process subject produces an effect on structure configuration of a semantically elementary simple sentence. Functional and semantic characteristics of the process predicates are outlined and their lexical groups are marked out. Considering the semantics of the process predicates the functional manifestation of the semantic and syntactic dependency of the process subject in Taras Shevchenko’s poetry has been described, their grammar and lexical manifestation has been studied. It is represented that the semantic and syntactic dependency of the process subject functions mainly in the nominative case, that has typical characteristics of weakening substantiality in comparison with the activity subject. The dependency of the process subject in the function of the nominative case has the multiform semantic potential that covers a wide range of human beings, creatures and objects.
Keywords: семантико-синтаксична структура речення; предикат процесу; семантико-синтаксична залежність суб’єкта процесу; компонент реченнєвої структури; semantic and syntactic structure of a sentence; a predicate of process; semantic and syntactic dependency of the process subject; a component of a sentence structure